Przegląd zastosowań analizy dyskryminacyjnej w badaniach marketingowych - Jefmański, Bartłomiej (The Review of Applications of Discriminant Analysis in Marketing Research, 2006)
Discriminant analysis is one of multivariate statistical data analysis methods used in marketing research. The aim of this paper is to present and analyse selected applications of discriminant analysis in marketing research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 107-119